The Bifunctional Catalase-Phenol Oxidase of Mycothermus Thermophilum (MtCATPO) Increases the Antioxidant Capacities of its Ortho-Diphenolic Substrates and of Green and Black Tea Extracts - Betül Söyler; Zümrüt Begüm Ögel (Turkish Journal of Agriculture: Food Science and Technology)
Catalase from the thermophilic fungus Mycothermus thermophilus is a bifunctional enzyme with a secondary phenol oxidase activity (CATPO). MtCATPO catalyses the oxidation of catechol, chlorogenic acid, caffeic acid and (+)-catechin to yield mainly dimers, and higher molecular weight oligomers and polymers. The role of this phenol oxidase activity is not known. Here, the antioxidant capacities (AC) of the phenolic substrates in the absence and presence of MtCATPO were compared. The oxidized products displayed enhanced AC reaching a maximum of 2.4-fold with catechol. Other phenol oxidases (laccase and tyrosinase) did not yield AC enhancement to the same extent. MtCATPO-treatment increased AC of green and black tea infusions, as well as water extracts of samples collected from a black tea production line up to 28%. The bifunctional MtCATPO appears to be an important antioxidant enzyme with a wide range of potential applications in the food, neutraceuticals and pharmaceuticals industry.